Implementing OECD BEPS Action Plan 4 in Indonesia, a comparative study with Malaysia - Havidz Ibrahim; Dahlia Sari (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
This study aims to provide ideal recommendations to implement BEPS Action Plan 4 in Indonesia. A comparative study was carried out on interest limitation rule in Indonesia and Malaysia using a black-letter approach. Furthermore, interviews and confirmation with relevant sources were also carried out. The study's findings demonstrate that it is appropriate to apply interest limitations that do not just apply to multinational corporations. However, Indonesia should use a limitation method based on a specified benchmark fixed ratio of net interest compared to EBITDA. Indonesia can also apply de minimis threshold to exclude the rule of limiting interest for taxpayers with low risk. Indonesia can use the highest benchmark fixed ratio according to OECD recommendations, namely 30% of EBITDA.